Penerapan LKPD Berbasis Project Based Learning pada Materi Translasi melalui Proyek Teselasi untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Peserta Didik - Annisa Qoyyima; Desi Ajarah; Mariatul Kiftia Shakila; Rani Nuldiva Situmorang (Universitas Palan, 2026)
This study aims to describe students’ mathematical creative thinking skills through the use of Project-Based Learning (PBL)-based Student Worksheets (LKPD) on the topic of translation via a tessellation project. The study employed a quantitative descriptive approach supported by qualitative data in the form of documentation of students’ project outcomes. The research subjects consisted of 20 students divided into 10 groups. Data were collected through the assessment of tessellation projects and documentation of students’ work, which were analyzed based on indicators of mathematical creative thinking skills, namely fluency, flexibility, originality, and elaboration. The results of the study indicate that students were able to generate various ideas in designing tessellation patterns, employ diverse pattern-arrangement strategies, and develop works demonstrating a visual understanding of the concept of translation. Elaboration skills were evident in the development of details, neatness, and refinement of the works, while originality was evident in the variety of motifs and designs produced by each group. Project-based learning provided students with the opportunity to explore ideas, collaborate in groups, and connect mathematical concepts with tangible products. The implementation of Project-Based Learning (PBL) in local curriculum materials through a tessellation project also helps students understand the concept of translation more concretely through activities involving the design and creation of repeating patterns. Overall, this approach facilitates the development of students’ creative mathematical thinking skills regarding the topic of translation and provides a more active, meaningful, and student-centered learning experience.